Hubungan Antara Kedisiplinan Belajar Dengan Hasil Belajar Mata Pelajaran Pendidikan Agama Islam di Kelas VI SD Negeri Nanggerang 01 - Clariska Rudianas Tiasari; Suhendra Suhendra; Rusdi Kasman (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
This research aims to determine learning discipline in Class VI of SD Negeri Nanggerang 01, to determine learning outcomes in Class VI of SD Negeri Nanggerang 01, to determine the relationship between learning discipline and learning outcomes of Islamic Religious Education subjects in Class VI of SD Negeri Nanggerang 01. This research is quantitative research and this research uses correlational methods. The research results show that student learning discipline data is included in the good category with a percentage of 52%. The research results show that student learning outcomes data is in the high category with a percentage of 81%. There is a positive and significant relationship between learning discipline and learning outcomes in Islamic Religious Education subjects in class VI of SD Negeri Nanggerang 01. This is shown in the magnitude of the correlation of 0.437 with a significant value of 0.000 <0.05, meaning that it shows there is a strong and significant relationship.